2017
DOI: 10.1002/ijc.30916
|View full text |Cite
|
Sign up to set email alerts
|

Prognosis of cancer in persons with infrequent consultations in general practice: A population‐based cohort study

Abstract: Cancer survival rates are lower in Denmark than in comparable European countries. This may partly be attributable to subgroups of cancer patients who seek medical attention at late disease stages. It is unknown if differences in usual (i.e. customary) consultation frequency in general practice are associated with cancer prognosis. We aimed to estimate the cancer prognosis of cancer patients stratified by their usual consultation frequency in general practice. We performed a population-based cohort study includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 45 publications
1
14
0
Order By: Relevance
“…Another major strength was the estimation of the patients' usual consultation frequency. The usual GP consultation rates of the cancer patients in this study were comparable to the usual rates of their sex‐ and age‐matched comparison subjects (Jensen et al, ), and this minimised the risk of misclassification of our main variable of interest.…”
Section: Discussionsupporting
confidence: 64%
See 4 more Smart Citations
“…Another major strength was the estimation of the patients' usual consultation frequency. The usual GP consultation rates of the cancer patients in this study were comparable to the usual rates of their sex‐ and age‐matched comparison subjects (Jensen et al, ), and this minimised the risk of misclassification of our main variable of interest.…”
Section: Discussionsupporting
confidence: 64%
“…The customary non‐attending patients in the present study have previously been shown to have a 40% higher risk of being diagnosed with more advanced disease stage and of dying prematurely when diagnosed with cancer later in life compared to attending patients (Jensen et al, ). Other studies of this population have shown that customary non‐attending patients seek help at the same point in time and to a similar extent as attending patients in the period just before the cancer disease, that is when the cancer disease can influence the patients' healthcare‐seeking behaviour (Jensen et al, ).…”
Section: Discussionmentioning
confidence: 55%
See 3 more Smart Citations